Prognostic Impact of Adjuvant Immunotherapy in Patients With Resectable NSCLC After Neoadjuvant Chemoimmunotherapy: A Brief Report - Yichen Dong, MD; Long Xu, MD; Jialiang Wen, MD; Haojie Si, MD; Juemin Yu, MD; Tao Chen, MD; Huikang Xie, MD; Xinjian Li, MD; Minglei Yang, MD; Junqiang Fan, MD; Junqi Wu, MD; Yunlang She, MD; et al. (JTO Clinical and Research Reports)
Objective: The potential survival benefits of adjuvant immunotherapy for resectable NSCLC after neoadjuvant chemoimmunotherapy, and the optimal number of adjuvant immunotherapy cycles, remain uncertain. This study aims to evaluate the prognostic impact of adjuvant immunotherapy and determine the optimal number of cycles. Methods: A total of 438 patients who received neoadjuvant chemoimmunotherapy between August 2019 and June 2022 across four hospitals were enrolled in this study, with a median follow-up time of 31.3 months. Recurrence-free survival (RFS) and overall survival (OS) were estimated using Kaplan-Meier methods and tested by log-rank test. Unstratified Cox proportional hazards models were fitted to the subgroups. Results: In this multi-center cohort, 29.7% of patients (n = 130) achieved a pathologic complete response. Patients who received adjuvant immunotherapy experienced significant survival benefits compared with those who did not (RFS: hazard ratio [HR] = 0.63, 95% confidence interval: 0.41–0.98, p = 0.037; OS: hazard ratio = 0.27, 95% confidence interval: 0.13–0.57, p < 0.001). Subgroup analyses found that patients with a squamous histologic type, positive PD-L1 expression, and those with a major pathologic response particularly benefited from adjuvant immunotherapy. In addition, we found that six cycles of adjuvant immunotherapy served as a threshold for better prognostic differentiation, suggesting that six or more cycles may be more beneficial. Conclusions: Our study found that the addition of adjuvant immunotherapy to neoadjuvant chemoimmunotherapy is significantly associated with improved RFS and OS in patients with resectable NSCLC. We also identified that six cycles of adjuvant immunotherapy may be the optimal regimen for these patients.